2012
DOI: 10.1104/pp.112.202127
|View full text |Cite
|
Sign up to set email alerts
|

Positive Regulation of psbA Gene Expression by cis-Encoded Antisense RNAs in Synechocystis sp. PCC 6803  

Abstract: The D1 protein of photosystem II in the thylakoid membrane of photosynthetic organisms is encoded by psbA genes, which in cyanobacteria occur in the form of a small gene family. Light-dependent up-regulation of psbA gene expression is crucial to ensure the proper replacement of the D1 protein. To gain a high level of gene expression, psbA transcription can be enhanced by several orders of magnitude. Recent transcriptome analyses demonstrated a high number of cis-encoded antisense RNAs (asRNAs) in bacteria, but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
79
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 88 publications
(84 citation statements)
references
References 40 publications
3
79
0
Order By: Relevance
“…4B, second and third panels). This is consistent with the protective function described for these antisense RNAs, which bind to the 5= untranslated regions (5=-UTRs) of their targets and thereby preventing degradation of the psbA2 and psbA3 mRNAs (47). The amounts of the flv4 mRNA and the as_flv4 antisense RNA were negatively correlated (Fig.…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…4B, second and third panels). This is consistent with the protective function described for these antisense RNAs, which bind to the 5= untranslated regions (5=-UTRs) of their targets and thereby preventing degradation of the psbA2 and psbA3 mRNAs (47). The amounts of the flv4 mRNA and the as_flv4 antisense RNA were negatively correlated (Fig.…”
Section: Resultssupporting
confidence: 73%
“…Moreover, the transcription initiation site of the antisense RNA kaiA-as1 does not interfere with the ribosome binding site of the kaiA mRNA (33). Theoretically, kaiA-as1 is able to bind within the 5=-UTR of kaiA mRNA to prevent mRNA degradation, as in the case of the antisense RNA PsbAR2 and the psbA2 mRNA (47). We find it interesting that in the phylogenetically quite remote marine organism Synechococcus sp.…”
Section: Discussionmentioning
confidence: 83%
“…MED134 (6). The drop in PR content during the stationary phase may be in part due to the promoter we selected, because it is known that psbA2 expression and transcript stability are light-intensity dependent (68)(69)(70)(71)(72)(73), and so is heterologous expression driven by this promoter (74,75). It is worth noting that several of the recently discovered proteorhodopsins in 'chemotrophic', often psychrophilic, bacteria only contribute detectably to growth rate or cell yield when the cells are stressed and/or in stationary phase (6,(14)(15)(16)(18)(19)(20).…”
Section: Discussionmentioning
confidence: 99%
“…An RNase III homolog in the heterocyst producing strain PCC 7120 that is closely related to A2542 in PCC 7002 was implicated in non-coding RNA mediated gene regulation (Gao et al 2013). Non-coding RNAs have been found to regulate many processes associated with photosynthesis in cyanobacteria (Georg et al 2014; Sakurai et al 2012; Eisenhut et al 2012; Duhring et al 2006). For example, Sakurai et al (2012) found that a cis -encoded antisense RNA can stabilize the psbA2 mRNA, encoding the photosystem II D1 protein, by inhibiting processing by RNase E. Therefore, we were surprised that the Δ 2542 strain did not exhibit a growth phenotype, even when in combination with Δ 0061 , which encodes the other full length RNase III homolog (Fig.…”
Section: Discussionmentioning
confidence: 99%